The Role of Social Media Live Streaming, Advertising and Affiliate Marketing on Purchase Intentions - Mohamad Afan Suyanto; Deby Rita Karundeng (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid development of e-commerce in Indonesia requires an in-depth understanding of the factors that influence consumer purchasing interest in online shopping. This study aims to examine the effect of live streaming, digital advertising, and affiliate marketing on consumer purchasing interest on online store platforms. Using a quantitative method with a survey approach, this study involved 657 respondents who were selected purposively because they had experience shopping online and were exposed to digital marketing strategies. Primary data were obtained through a Google Forms-based questionnaire with a 5-point Likert scale, which had been tested for validity and reliability. Data analysis was carried out using Structural Equation Modeling Partial Least Squares (SEM-PLS) using SmartPLS 3 software. The results showed that live streaming, digital advertising, and affiliate marketing had a positive and significant effect on purchasing interest. Interactive live streaming increases consumer trust and purchase intention. Creative and relevant digital advertising attracts attention and builds emotional connections with consumers. Affiliate marketing by credible third parties supports purchasing decisions through honest and informative reviews. This study provides valuable insights for academics and digital marketing practitioners, emphasizing the important role of technology-based promotional strategies and social engagement in driving purchasing interest in the digital era.